Dampak Penggunaan QRIS Terhadap Kepuasan Konsumen Sebagai Alat Transaksi - Purnama Ramadani Silalahi; Khairina Tambunan; Tryana Ramadhany Batubara (CV. Ulil Albab Corp, 2022)
The use of payment instruments has made very significant progress. The change is in the form of a digital payment tool that is very helpful and accelerates the payment process and helps reduce physical contact as a form of reducing the spread of the Covid-19 virus which can be attached to paper money as a means of payment. QRIS is the Indonesian Quick Response Code Standard, which is the National QR code standard as a payment medium for QR codes in Indonesia, which was launched by Bank Indonesia. Using one E-Wallet as a means of payment for several merchants such as Link Aja, Gopay, OVO, DANA, ShopeePay and others is very helpful as a means of payment transactions. Where physical to digital payment instruments are easy, effective and efficient, easy to implement and able to integrate with software that uses the InterActive QRIS Open API Platform. This research was conducted based on a quantitative approach with a causal study research method, namely a study conducted to state that the independent variable causes or affects the dependent variable. Data was collected through interviews, observations and distributing questionnaires.